Suburban urbanism : discovering a South African suburbia - Kara, Muneebah (My University, 2014)
There is a consensus amidst the planning community that we are currently experiencing a sweeping paradigm shift; which has over the last forty-years gained rapid momentum. Postmodernism is proposed to have prompted a return to ‘the small is beautiful’ and the revaluation of people as the critical and central receptors of the spaces that past and present planners produce. An emphasis on the everyday and lived experience of the urban population is just another symptom in the argument for postmodernism. As perhaps is common with all paradigm shifts, along with the transformation has come a flurry of some new terminologies and a redefining of others. Suburban neighbourhoods have experienced an interrogation of terminology; and epistemological and phenomenological value. The identification of inner-circle suburbs is just one of the many terms to describe a uniquely urban space within the once blanketing term ‘suburbs’. Inner-circle suburbs are often the oldest suburbs in an urban area and are located closest to the Central Business District. A revitalised inquisition in suburban spaces has prompted new and creative ways of exploring the suburbs; with our own locally grown urbanists showing interest and producing knowledge on the dynamics of South African suburban neighbourhoods. Needless to say, this is still a relatively young topic that favours an investigation into spatial form and structure over the significance of the lived practice. This research report is an attempt to coalesce the spatial form and practiced living into a single coherent snap-shot of the lives of northern inner-circle suburban dwellers.
A research report submitted to the Faculty of Engineering and the Built Environment: University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Development Planning
Keywords: City planning--South Africa.; Suburbs--South Africa--Planning.